Investigation of helicopter loading spectra variations on fatigue crack growth in titanium and aluminium alloys - Buller, Richard Gregory (Cranfield University, 1999)
An investigation has been made into the effect of omitting small, vibratory load cycles from a helicopter load spectrum on the fatigue crack growth rates of high strength titanium (Ti-lOV 2Fe 3A1) and aluminium (7010 T73651) alloys. The investigation is made in the light of new requirements for the damage tolerance design of transport helicopter structures that have normally been designed to safe life criteria. The work aims to improve the damage tolerance design of helicopter structures by understanding the contribution of the vibratory load cycles to fatigue crack growth damage. The experimental work consisted of two parts that considered fatigue crack growth under simple overload type loading and complex fatigue load sequences using compact tension specimens. Simple overload and underload tests were run under near-threshold, plane strain crack growth rates typical of those experienced in helicopter components. These were supplemented by crack closure measurements made using a strain gauge adhered close to the crack tip. Fatigue crack growth rate retardation was observed after an overload and this was reduced if a tensile underload was subsequently applied. The experimental evidence suggested that observed crack growth transient behaviour could be explained by a residual stress field mechanism ahead of the crack tip with closure only serving in a secondary role to modify the applied external loading. A fatigue load sequence was developed for a helicopter rotorhead component and included representations of manoeuvre loads superimposed with the high mean stress, vibratory load cycles. A technique of progressively omitting small load cycles of increasing range from this sequence was used to determine the effect of these cycles on the fatigue crack growth. It was found that the these cycles of 16% range caused up to 80% of the total crack length damage and that the observed crack growth rate of the cycles was three times greater than that predicted by a conservative fatigue crack growth model. These are significant observations because vibratory cycles are usually considered to be non-damaging under a safe life design to which most current transport helicopters have been certified to. It was proposed that the accelerated growth rate of these cycles was caused by frequent underloads in the rotorhead loading sequence. A residual stress field model was invoked to explain this behaviour. The results are used to provide guidance for damage tolerant design of helicopter structures.